Materiality in reporting of Shari’ah non-compliant income for Malaysian Islamic Banking Institutions / Norhanizah Johari … [et al.] - Johari, Norhanizah; Kasim, Nawal; Mohd Ali, Nor Aishah; Mohd Shairy, Mohd Zikri; Mohd Arshad, Roshayani (Faculty of Accountancy, 2019)
Materiality in financial reporting is concern with whether an omission or a misstatement of such information would influence the economic decisions of financial statements users. An item is considered material, if it is capable of making a difference in the economic decision made by a user. Thus, materiality should be assessed not only in relation to the size of an item, but also to the nature and incidence of the item occurring. An item that is otherwise insignificant in size may be a material item. Therefore, judgments is required in deciding which items shall be considered as material or immaterial. Information is material if omitting it or misstating it could influence the decisions made by the primary users of a specific reporting entity. In other words, materiality is an entity-specific aspect of relevance based on the nature or magnitude, or both, of the items to which the information relates in the context of an individual entity’s financial report. This newly definition on materiality issued by MASB in 2018, will be referred as a basis of comparison with the previous concept of materiality issued by the board before. This study will explore how the concept of materiality viewed by the Islamic Banking Institutions (IBI) in Malaysia particularly for the reporting of the Shariah Non-Compliant Income in the IBIs annual report for the year 2016 until 2018. It is expected that the findings will embark on the materiality as a very important element of reporting particularly in the reporting of SNCI for the sustainability of the IBIs. The outcomes of this study is expected to benefit the policy makers, the IBIs, the accounting profession and the financial statement users with regards to the financial reporting of IBIs in Malaysia, where materiality of SNCI is the central issue of discussion of this paper.